2009
DOI: 10.3109/10611860903115308
|View full text |Cite
|
Sign up to set email alerts
|

Mannosylated nanoparticulate carriers of rifabutin for alveolar targeting

Abstract: The objective of the present study was to evaluate the prospective of engineered nanoparticles for selective delivery of an antituberculosis drug, rifabutin, to alveolar tissues. Drug-loaded solid lipid nanoparticles (SLNs) were synthesized and efficiently mannosylated. The formation of uncoated and coated SLNs was characterized by FTIR spectroscopy and SEM studies. A variety of physicochemical parameters such as drug loading, particle size, polydispersity index, zeta potential, and in vitro drug release were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(51 citation statements)
references
References 28 publications
2
44
0
1
Order By: Relevance
“…It is more challenging for delivery of drugs to central nervous system (CNS) and brain but NPs and neuropeptides can over comes these problems and the drug can be delivered in the brain successfully through the carrier such as hexapeptide dalargin, dipeptide kyotorphin across blood brain barriers (BBB) through endocytosis by endothelical cell lining of the brain blood capillaries. Nimje [59] impart that NPs can be used as carrier such as mannose conjugated solid lipid NPs (SLNPs) that can be exploited for effective and targeted delivery of rifabutin. [60].…”
Section: Microencapsulation Of Nanoparticlesmentioning
confidence: 99%
“…It is more challenging for delivery of drugs to central nervous system (CNS) and brain but NPs and neuropeptides can over comes these problems and the drug can be delivered in the brain successfully through the carrier such as hexapeptide dalargin, dipeptide kyotorphin across blood brain barriers (BBB) through endocytosis by endothelical cell lining of the brain blood capillaries. Nimje [59] impart that NPs can be used as carrier such as mannose conjugated solid lipid NPs (SLNPs) that can be exploited for effective and targeted delivery of rifabutin. [60].…”
Section: Microencapsulation Of Nanoparticlesmentioning
confidence: 99%
“…Similar results have been observed by others, studying conjugation of mannose onto SLNs, polypropyleneimine dendrimers, etc. [243][244][245].…”
Section: Macrophage Targetingmentioning
confidence: 99%
“…Results of in vivo toxicity studies showed that capreomycin oleate exhibited its lowest toxic potential suggesting it be used as super generics in pulmonary tuberculosis treatment [73]. Outcomes of various miscellaneous lipid based drug delivery systems in the treatment of TB are summarized in Table 6 [74][75][76][77][78][79][80][81][82][83][84][85][86].…”
Section: Miscellaneous Lipid Based Formulationsmentioning
confidence: 99%